ANALISIS KEMAMPUAN LITERASI MEMBACA DAN LITERASI NUMERASI PESERTA DIDIK KELAS XI SMA PADA MATERI SUHU DAN KALOR DALAM PENGEMBANGAN SOAL ASESMEN KOMPETENSI MINIMUM (AKM) - Niza, Alvin Khoirun; Zainuddin, Abu (Universitas Negeri Surabaya, 2024)
The Minimum Competency Assessment (AKM) is part of the national assessment to measure minimum competency in reading literacy and numeracy. AKM questions consist of several cognitive levels. This quantitative descriptive research aims to analyze students' reading literacy and numeracy literacy skills in solving AKM questions in a scientific context in the field of physics regarding temperature and heat. The research was conducted in May 2024 at one of the state high schools in Sidoarjo Regency. The population in this study were 2 classes, namely XI 1 and XI 2, totaling 70 students. Data collection used interviews, questionnaires and AKM test instruments. The instrument used is the AKM test developed with a valid category and a reliability value of 0.701. The results of this research show that the minimum competency of most students is at the basic level at 31.43%, meaning that students have basic concepts, but have difficulty applying these concepts in real situations. The percentage of students in the proficient category is 28.57%, each in the proficient and need special intervention categories is 20%. Achievement of the greatest cognitive level of reading literacy at the level of evaluating and reflecting (evaluate and reflect) because the stimulus phenomena in the questions are often encountered by students. Achievement of the highest cognitive level of numeracy literacy at the application level (applying) because students are able to determine appropriate strategies and formulas in solving the problems presented in the questions. Keywords: Minimum Competency Assessment (AKM), Reading Literacy, Numeracy Literacy, Temperature and Heat